2013
DOI: 10.1186/1749-799x-8-30
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac and triamcinolone acetonide impair tenocytic differentiation and promote adipocytic differentiation of mesenchymal stem cells

Abstract: BackgroundTendinopathies are often empirically treated with oral/topical nonsteroidal anti-inflammatory medications and corticosteroid injections despite their unclear effects on tendon regeneration. Recent studies indicate that tendon progenitors exhibit stem cell-like properties, i.e., differentiation to osteoblasts, adipocytes, and chondrocytes, in addition to tenocytes. Our present study aims at understanding the effects of triamcinolone acetonide and diclofenac on tenocytic differentiation of mesenchymal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…It was noted that methylprednisolone suspension in culture media was a more basic pH than that of the other drugs studied. Previous in vitro studies have also suggested that corticosteroid exposure can inhibit the regenerative properties of human tendon stem cells and may also augment undesirable adipogenesis in murine MSCs . When considering these reasons and the poor viability demonstrated in the current study, the authors would strongly advise against treating with corticosteroids immediately after stem cell treatment.…”
Section: Discussionmentioning
confidence: 85%
“…It was noted that methylprednisolone suspension in culture media was a more basic pH than that of the other drugs studied. Previous in vitro studies have also suggested that corticosteroid exposure can inhibit the regenerative properties of human tendon stem cells and may also augment undesirable adipogenesis in murine MSCs . When considering these reasons and the poor viability demonstrated in the current study, the authors would strongly advise against treating with corticosteroids immediately after stem cell treatment.…”
Section: Discussionmentioning
confidence: 85%
“…14 Different concentrations of ascorbic acid are used in tenocyte cultures to enhance collagen synthesis. 9,15 Immunofluorescence staining revealed differential localization of type I collagen in vitro, with collagen localized outside cells in the presence of ascorbic acid. 16 Poulsen et al reported in 2011 that ascorbic acid can protect hamstringderived tenocytes from oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…The standard growth medium with fetal bovine serum containing 25 µg/mL ascorbic acid was found to be the most suitable formulation [29]. Additionally, 1250 µg/mL ascorbic acid played an important role during cell culture [30], and 50 µg/mL ascorbic acid is believed to support proper collagen synthesis [31]. Furthermore, cotreatment of tenocytes with ascorbic acid protects against the glucocorticoid-induced inhibition of ERK and Akt activation and the reduction in cell number induced by chemical inhibition of ERK, and, to a lesser extent, inhibits Akt signaling [21].…”
Section: Discussionmentioning
confidence: 99%